El experimento democrático: reflexiones sobre teoría política y ética cívica. - Falla Carrillo, Ricardo L. (Sílex, 2021)
This text sets out to examine the dilemma of the 2021 second round of elections in terms of a tragic conflict. Both electoral options pose authoritarian political proposals that violate the principles and practices of liberal democracy. As Polybius warned, the corruption of democracy leads to the oclocracy, a political figure that dissolves all forms of institutionality that produces the tyranny of the crowd. The only way to face this danger lies in the recovery of civic ethics, as well as the reconstruction of historical memory.